Prevalence of anatomical/orthopedic disorders and effective factors in children aged 6–14 years - Çetin, Aymelek; Mete, Burak (Indian Journal of Child Health, 2018)
Background: Musculoskeletal disorders are common among children. Community- and school-based studies have revealed that the complaint of pain in childhood associated with musculoskeletal deformities is common. Objective: The present study aims to examine the prevalence of extremity, spinal and chest wall deformities and other disorders in children aged 6–14 years, and to determine the relationship between these disorders and nutrition, benefiting from sunlight, and familial factors. Method: The present cross-sectional study was conducted among 625 children aged 6–14 years attending elementary and secondary schools in rural, urban, and suburban areas. Children were evaluated for kyphosis, scoliosis, lordosis, chest wall disorders, and other disorders. Families were also asked about the factors that may be associated with these disorders. Chi-square test and binary logistic regression test were used for data analysis and p